Philosophy 167: Class 8 - Part 4 - The Significance of Descartes' Principia- Its Influence, and the Reconceptualization of Curvilinear Motion. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Overview of Descartes' Principia Philosophiae and Descartes' reconceptualization of curvilinear motion.; Opening line: "All right, so the Principia, let's spend the rest of our time on Descartes save for one letter he wrote, that we'll look at next week."; Duration: 11:21 minutes.; Segment: Class 8, Part 4.